African politics of survival : extraversion and informality in the contemporary world - Endo, Mitsugi; Onoma, Ato Kwamena; Neocosmos, Michael (LANGAA RPCIG, 2021)
"This volume addresses two primary research concerns: first, considering extraversion (or extroversion) as a term for characterizing a region that is "mobilizing resources from their (possibly unequal) relationship with the external environment", a dynamic that constitutes a possible African potential; and, second, a survey of competing systems and strategies with a focus on relationships between formal and informal institutions in terms of their collaborations and conflicts. In addition, this volume contains three chapters examining very recent African responses to the ongoing COVID-19 pandemic from a variety of perspectives. The final part of this volume contains an important contribution to the conceptualization of 'African Potentials'. This has proven to be a significant conceptual innovation, that allows intellectual access to alternative ways of thinking about latent ideas of universality."-Back cover.